ANALYZING THE STUDENTS’ WRITING PROFICIENCY THROUGH CAREER EXPLORATION TECHNIQUE AT STKIP MUHAMMADIYAH BULUKUMBA - Emirati Emirati; Mutmainnah Marzuki (Universitas Muhammadiyah Makassar, 2021)
One of effectives technique that used by the teacher is Career Exploration Technique where it was affords as a systematic procedure by the teacher could guide the students to write. Career exploration is an activity, guide, and counseling to assist students make decisions about choosing their future professions, and how to get jobs in their chosen fields (Kelly, 2010). The teacher could guide students to express and write down their ideas in choosing a job in the future. As opinion of the researcher that one of the best ways to stimulate the students’ idea is facilitate them by giving the material that is closest to their life and the closest thing is about themselves.This research will use Quasi-experimental design as a method which involves two groups; an experimental group and control group. The population of this research is the fourth semester of English Education at STKIP Muhammadiyah Bulukumba in 2018-2019 academic years. There are two classes namely 18 A that consist of 23 students and 18 B that consist of 27 students, so the total number of population is 50 students. It will be taken by using total technique sampling. So, the sample of this research is 18 A for control group and 18 B for experimental group. During the research, the researcher will apply Career exploration technique in writing class. The purpose of this research is to find out the effectiveness of Career exploration technique in teaching writing course.